ISM AL-TAFḌĪL DALAM AL-QUR‘AN JUZ 11 SAMPAI 20 (ANALISIS MORFOSINTAKSIS): Comparative noun in Quran in JUZ 11 until 20 (Morphosintax Study) - Nafi', Syihabudin; Ahmad Miftahuddin; Hasan Busri (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
The comparative degree in the Arabic language is known by the term "ism al tafdhil." Ism al-tafdhil is an attribute formed by following the pattern أَفْعَلُ for masculine and فُعْلى for feminine, indicating that there are two entities with a shared attribute, but one surpasses the other in that quality. Ism al tafdhil possesses uniqueness in its formation both morphologically and syntactically. The objectives of this research are: (1) to identify ism al tafdhil in the Quran from Juz 11 to 20, (2) to explain the formation of ism al tafdhil in the Quran from Juz 11 to 20, (3) to describe the types of ism al tafdhil in the Quran from Juz 11 to 20, (4) to describe the cases and syntactic functions of ism al tafdhil in the Quran from Juz 11 to 20, and (5) to describe the grammatical markers of ism al tafdhil in the Quran from Juz 11 to 20. This research is qualitative and employs a library research design. The data consist of ism al tafdhil in the Quran from Juz 11 to 20. Data collection is done through documentation techniques, while purposive sampling is used for sample selection. The instruments used include data cards and recapitulation sheets. The results of the study reveal that there are 318 instances of ism al tafdhil in the Quran from Juz 11 to 20. Based on the formation of ism al tafdhil, the researcher finds 238 instances formed by changing the basic form following the pattern أَفْعَلُ, 77 instances following the pattern فُعْلَى, and 3 instances formed by changing from the basic form into the original nominal stem (mashdar) with the addition of ism al tafdhil directly from a qualifying word. Regarding the types of comparative degrees, 163 instances take the form of comparative, and 155 instances take the form of superlative. Based on the structure of ism al tafdhil, 260 instances are non-compound (not idhafi) and not preceded by ال, 89 instances are preceded by ال, 13 instances are compound idhafi with the mudhaf ilaih being a definite (nakirah) noun, and 56 instances are compound idhafi with the mudhaf ilaih being a definite (ma’rifah) noun.